HCFC1 is a common component of active human CpG-island promoters and coincides with ZNF143, THAP11, YY1, and GABP transcription factor occupancy - Michaud, Joëlle; Praz, Viviane; Faresse, Nicole James; JnBaptiste, Courtney K.; Tyagi, Shweta; Schütz, Frédéric; Herr, Winship

(untitled) (Genome Research, 2013)
In human transcriptional regulation, DNA-sequence-specific factors can associate with intermediaries that orchestrate interactions with a diverse set of chromatin-modifying enzymes. One such intermediary is HCFC1 (also known as HCF-1). HCFC1, first identified in herpes simplex virus transcription, has a poorly defined role in cellular transcriptional regulation. We show here that, in HeLa cells, HCFC1 is observed bound to 5400 generally active CpG-island promoters. Examination of the DNA sequences underlying the HCFC1-binding sites revealed three sequence motifs associated with the binding of (1) ZNF143 and THAP11 (also known as Ronin), (2) GABP, and (3) YY1 sequence-specific transcription factors. Subsequent analysis revealed colocalization of HCFC1 with these four transcription factors at ∼90% of the 5400 HCFC1-bound promoters. These studies suggest that a relatively small number of transcription factors play a major role in HeLa-cell transcriptional regulation in association with HCFC1.